1995
DOI: 10.1148/radiology.195.2.7724767
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of pseudoaneurysm after diagnostic and therapeutic angiography.

Abstract: The incidence of pseudoaneurysm after transfemoral arterial catheterization depends on the type of intervention. The main risk factor is too brief a period of manual compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
2
6

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(124 citation statements)
references
References 0 publications
1
115
2
6
Order By: Relevance
“…There were recurrences in a total of 10 patients who subsequently underwent repeat USGC 8 or surgery. 2 We later demonstrated that USGC was successful in 56 (73%) of 77 patients who received anticoagulation. Seven (12.5%) of these patients required 2 or 3 compression attempts to induce sustained thrombosis.…”
Section: Ultrasound-guided Compressionmentioning
confidence: 90%
See 1 more Smart Citation
“…There were recurrences in a total of 10 patients who subsequently underwent repeat USGC 8 or surgery. 2 We later demonstrated that USGC was successful in 56 (73%) of 77 patients who received anticoagulation. Seven (12.5%) of these patients required 2 or 3 compression attempts to induce sustained thrombosis.…”
Section: Ultrasound-guided Compressionmentioning
confidence: 90%
“…In 1 series where diagnostic ultrasound was performed on 536 consecutive patients who underwent catheterization, the incidence of PSA was 7.7%, with 83% of the PSAs associated with interventional procedures. 2 Despite a low incidence, PSAs are commonly encountered when more complex coronary and peripheral interventions are performed, especially with the use of potent antithrombotic and antiplatelet therapy. Since 1996, the number of peripheral interventions has more than doubled to an estimated 750 000 procedures in 2005.…”
mentioning
confidence: 99%
“…Prospective series which screen every post-angiography groin tend to report higher incidences (7.7%, 6%). 12,13 Those patients who develop FA tend to be anticoagulated at the time of the development of the lesion (78%). 13 Kent et al tried to establish the natural history of 16 patients with clinically detected FAs and offered surgery only for symptoms doubling in size or persistent patency over a two-month period.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Psö do a nev riz ma in si dan sı nı ar tı ran fak tör ler ara sın da ponk si yon tek ni ği, kom pres yon tek ni ği, kul la nı lan she at ka lın lı ğı gi bi an ji og ra fi uy gu la yı -cı sı na bağ lı özel lik ler var dır. Bir kıs mı ise yay gın pe ri fe ral ar ter has ta lı ğı, hi per tan si yon, obe si te, anti ko a gü lan kul la nı mı, trom bo si to pe ni gi bi has ta ile il gi li fak tör ler dir.…”
Section: Tar Tiş Maunclassified